Strategi Pengembangan Usahatani Gaharu di Kabupaten Oku Timur - Al Furqany; Fifian Permata Sari; Munajat Munajat (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to analyze the internal and external factors of agarwood farming and to formulate appropriate development strategies in East OKU Regency. The research employed a survey method with a census sampling technique involving all agarwood farmers. The analytical tools used were the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, and SWOT analysis to determine strategic positioning. The study was conducted in January 2026. The results indicate that internal factors include the availability of potential land resources, farmers’ experience, and the development of farmer institutions. External factors consist of market demand, relatively high and stable prices, government support, post-harvest processing potential, and partnership opportunities, while threats include price fluctuations, strict trade regulations, pests and diseases, climate change, and competition. Based on the SWOT and IE matrix analysis, agarwood farming is positioned in Quadrant I (aggressive strategy). The recommended strategy is the development of post-harvest processing to enhance value added and competitiveness in a sustainable manner.